LITERATUR REVIEW: FAKTOR LINGKUNGAN DAN KEPADATAN LARVA ANOPHELES DENGAN KEJADIAN MALARIA - Yana Afrina; Mursid Raharjo; Nurjazuli Nurjazuli (Poltekkes Kemenkes Bandung, 2021)
Malaria is an infectious disease caused by the protozoan plasmodium parasite and transmitted through the bite of the Anopheles mosquito. About 212 million cases of malaria occur globally and 429,000 died in 2015, most of them children under the age of 5. Approximately 91 countries were still endemic to malaria in the world at the beginning of 2016, the areas with the highest malaria problems were in parts of Africa, the Americas, the Middle East and Asia. The purpose of this study was to determine the relationship of environmental factors and the density of Anopheles larvae with the incidence of malaria. This type of research is literature reviewed with systematic analysis and assessed with the suitability of the desired topic and criteria. Based on the results of 12 studies found that, the most dominant risk factors associated with the incidence of malaria are environmental factors, including the physical environment, biological environment, chemical environment, and socio-cultural. Based on 5 studies on the density of larvae Anopheles found that breeding sites favored by Larvae Anopheles such as swamps, ponds former digs, lagun, trenches, abandoned fish ponds, river estuaries and rice fields.